PENGARUH KUALITAS LAYANAN DAN SUASANA TOKO TERHADAP KEPUASAN PELANGGAN TOKO TOYS CITY MALL SUMARECON, BEKASI - Achmad Nizar Thaib; Dr. Ismail Razak, M.Si.; Nuridin (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2020)
This study aims to determine the effect of service quality and store atmosphere on customer satisfaction at Toys City Mall Summarecon Bekasi. This research is a quantitative research and survey research. The population of this study is the customer-owner owner of children's toys buyers Toy City Mall Mall Summarecon Bekasi. The number of samples is 60 respondents, while the sampling technique uses the saturated sample technique. The data of this research are primary data sourced from questionnaires that have been tested for validity and reliability, while the data analysis uses descriptive statistical analysis, simple and multiple regression, hypothesis F test and hypothesis test t. The results of this study indicate that: 1) Service quality has a positive and significant effect on customer satisfaction at Toys City Mall Summarecon Bekasi. 2) The atmosphere of the store has a positive and significant effect on customer satisfaction at the Toys City Mall Mall Summarecon Bekasi. 3) Service quality and store atmosphere together have a positive and significant effect on customer satisfaction at Toys City Mall Summarecon Bekasi..